PARATEXTS AS A CONSTRUCTION SPACE FOR THE BOOK PUBLISHING MEMORY - Freire, Deolinda de Jesus (2019)
The process which transforms the manuscript into a book object, understood in this study as materiality, allow us to notice the elements that contribute to the construction of the book publishing memory. These elements are divided into two groups, being the first composed by resources considered ornamental, whose role is to make the layout and organization of the text more pleasurable. The second group is composed by preliminary speeches authors and officers, which together engender a place characterized by the meeting between the text and the reader. These preliminary texts, along with the ornamental elements, are treated by critics as paratext. The princeps edition official speeches of Historia de la conquista de México by Dom Antonio de Solís, published in 1684, proves that the manuscript was evaluated by nine instances before being published as a book. Considering that the ruled world of the sixteenth century is reflected in the book editions, as well as in the discourses that legitimize it, this paper intends to think the paratexts of the Historia by Solís as a space for the construction of the work publishing memory from the censorship of Don Gaspar de Mendoza Ibáñez de Segovia, which is one of the official speeches.